Respuesta :

Answer:

[tex]a^{-7}[/tex]

Step-by-step explanation:

using the rule of exponents

[tex]\frac{a^{m} }{a^{n} }[/tex] = [tex]a^{(m-n)}[/tex] , then

[tex]\frac{a^{-13} }{a^{-6} }[/tex]

= [tex]a^{(-13-(-6))}[/tex]

= [tex]a^{(-13+6)}[/tex]

= [tex]a^{-7}[/tex]

Answer:

[tex]a^-7[/tex]

Step-by-step explanation:

[tex]\frac{a^m}{a^n}=a^{(m-n)}, then[/tex]

[tex]\frac{a^{-13} }{a^{-6} }[/tex]

[tex]=a^{(-13-(-6))}[/tex]

[tex]=a^{(-13+6)}[/tex]

[tex]=a^{-7}[/tex]

Otras preguntas

ACCESS MORE